2020
DOI: 10.2185/jrm.2019-006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence patterns of alcohol consumption and factors associated with problematic drinking on remote islands of Okinawa, Japan: a cross-sectional study

Abstract: Objective: This study aims to investigate the drinking behavior on the remote islands of Okinawa Prefecture. Patients/Materials and Method: This was a cross-sectional study conducted with residents of Okinawa Prefecture's small, isolated islands. Between October 1 and December 3, 2014, island residents over 20 years of age who visited island clinics for an annual health checkup or influenza vaccination were recruited. An anonymous entry survey was administered to those who provided their consent. The survey in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…One possible reason for this is the low statistical power owing to the low prevalence of smokers and drinkers. However, the prevalence of problematic alcohol drinking in Okinawa was much higher than that in a national survey in Japan 41 . Thus, the questionnaire and interview might fail to detect actual smoking and drinking habits because of underreporting based on the social norms that pregnant women should avoid.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…One possible reason for this is the low statistical power owing to the low prevalence of smokers and drinkers. However, the prevalence of problematic alcohol drinking in Okinawa was much higher than that in a national survey in Japan 41 . Thus, the questionnaire and interview might fail to detect actual smoking and drinking habits because of underreporting based on the social norms that pregnant women should avoid.…”
Section: Discussionmentioning
confidence: 84%
“…However, the prevalence of problematic alcohol drinking in Okinawa was much higher than that in a national survey in Japan. 41 Thus, the questionnaire and interview might fail to detect actual smoking and drinking habits because of underreporting based on the social norms that pregnant women should avoid. Furthermore, we found a significant relationship between alcohol consumption and the high prevalence of dropout in the 20s age group, but not in other age groups (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the religion that they follow on the societal level of alcohol use has been stated in many published manuscripts. 17,26 Those who go to a religious place are less likely to go there to practice alcohol abuse. As compared to never going, the interview results also showed that the student's alcohol usage was due to family history factors or their personality and peer influences that exposed them to being alcohol addicted.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the obvious challenges of adapting these diets to the general population, investigating the Blue Zones' eating regimes and their historical evolution makes for an exciting field of study. Subtropical [8] Mediterranean [8] Mediterranean [8] Tropical [8] Daily energy intake per capita (kcal) < 2000 [31] <1500 [88] 2,600 [58] 2,392 [89] Obesity rate (%, BMI ≥ 30 kg/m²) 10-40 [90] 12.5 [88] 9.8 [91] 23.6 [76] Frequency of intake in times/wks* Vegetable Fruits Total dairy Meat, poultry Fish Alcoholic beverages 5.0 4.0 3.0 1.0 0.5 ++ [92] 4.1 4.8 n.a. 1.5 1.8 + [9] 2.3 3.2 6.4 1.5 0.4 ++ [9] 6.1 4.5 3.6 3.2 1.3 ++ [76] Hardness in drinking water ++ [37] - [93] + [94] +++ [80,81] *Authors' elaboration from different sources…”
Section: Discussionmentioning
confidence: 99%